Analisis Pengaruh Corporate Governance, Profitabilitas, Capital Intensity Terhadap Agresivitas Pajak - Amilia Nofitasari; Wiwin Wahyuni (LPPM Universitas Wijaya Kusuma Surabaya, 2024)
The purpose of this research is to find out how much influence the relationship between Tax Aggressiveness has on Corporate Governance which is proxied by the Board of Directors, Board of Independent Commisioners, Institutional Ownership and Audit Committee, Profitability, Capital Intensity. This research is quantitative research using secondary data obtained from annual financial reports on the BEI website www.idx.co.id . The population of this research was 38 companies from 2020-2022. The sampling technique for this research uses a purposive sampling technique. The samples obtained were 144 samples. The method used in this research is multiple linear analysis using SPSS 23 for statistical analysis. The results of this research show that Corporate Governance as proxied by the Board of Directors, Board of Independent Commissioners, Institutional Ownership, Audit Committee, has a but not significant effect on Tax Aggressiveness. Meanwhile, Profitability has a on Tax Aggressiveness.